Outside Back Cover: Volume 4 Issue 2. Issue 2 (27th December 2022) - Gan, Linli; Zeng, Zhen; Lu, Haojie; Li, Daiqi; Wei, Ke; Cai, Guangming; Zhang, Yingying
Abstract : Outside back cover image : Electronic fibers/textiles have great potential for applications in smart wearables due to their excellent flexibility, air permeability, and wearing comfort. In this work, a continuous, large‐scalable spraying‐spinning process for fabricating reliable and durable multifunctional electronic yarns is reported. The process can be applied with various raw fiber materials and is compatible with traditional textile processes. The as‐prepared yarns show excellent mechanical durability, washability, good conductivity and multiple electronic functions, enabling its versatile applications in smart textiles. This spraying‐spinning process for electronic yarns may play important roles in the development of practical smart fibers/textiles. (DOI: https://doi.org/10.1002/smm2.1151 )